The importance of planning and its role as a modern training method for achieving good performance among adolescent handball players - Merichiche, khaled; medjadi, MEFTAH (sports creativity, 2025)
Undoubtedly, a good result comes after considerable effort, and this effort cannot be haphazard; it requires planning and prior calculations. In other words, we can say that well-thought-out and effective work produces a good outcome. Therefore, good athletic performance requires a well-thought-out and pre-planned scientific strategy implemented by the coach. Anyone following Algerian sports will notice the poor and declining performance of Algerian football, especially handball, over the last decade, compared to other African and international countries. In handball, skillful performance plays a significant role in achieving positive results for the team. It also directly influences the mastery and success of the team's playing style, leading to the opponent's confusion and hindering their ability to perform at their best, thus enabling a simple victory. Skill development in handball is a fundamental aspect of the training process, and this development requires well-thought-out methods and means that are planned in advance by the team's management. Planning allows us to predict future events. It involves anticipating all possible reactions and taking them into account in advance in a coordinated manner, choosing between viable alternative approaches. Planning is also defined as the process of intellectually predicting an activity an individual wishes to perform. It is considered a project outlining the structure, content, and conditions of the training process, a project that is continuously developed and improved. Kockooshken states regarding prediction and planning for the development of physical education and sports that prediction in physical education and sports is a deliberate forecast of changes in the main direction and outcomes. This development is based on established and available resources. Based on all of this, we wanted to link the general planning process to the sports training process in handball, and we focused our study on adolescents.